Validation of Patient Satisfaction Scale and Measurement of Patient Satisfaction Level Among Inpatient of a Tertiary Care Hospital, Chengalpattu District Tamil Nadu - R, Ranjana; VV Anantharaman; Palanisamy, Kaveri; K Bincy; M, Manoharan (National Journal of Community Medicine, 2023)
Background: Patient satisfaction is crucial for research, administration, and planning. Since it reveals the effectiveness of the provider, customer happiness is of utmost importance as a gauge of the quality of service. Inpatient satisfaction is an essential tool to identify the level of patient satisfaction and it is one of the important goals of any healthcare system. The objective of the study is to validate the questionnaire developed and to assess the inpatient satisfaction level among patients admitted to OBG ward in a tertiary care hospital. Methods: A cross-sectional study was done among 160 women inpatients admitted in the OBG ward in a tertiary care hospital, Chengalpattu. Patient satisfaction was measured by a validated questionnaire with seven domains, the data were collected by face-to-face interview method. Results: The mean age of the respondent were 28 years. 60% of respondents were highly satisfied with the effectiveness of the treatment. Only 33.8% of respondents were highly satisfied with the diet food served and 56.3% were highly satisfied with the cleanliness of wards, and restrooms. Conclusions: The results obtained from the present study can serve as a baseline to compare the future survey and helps to provide healthcare services that fulfil patient desires and expectations.